Selection of the Optimal Regular Development Scheme under Conditions of Considerable Geological Uncertainties; Через интеграцию геонаук - к постижению гармонии недр - Nazmutdinov A. F. Aydar Floridovich (Risk and Uncertainty Analysis, 2016)
Title screen